BIOLOGICAL EVALUATION AND MOLECULAR DOCKING STUDIES OF LINKED ZEIN NANOPARTICLES - Adlin Janeefa.J; DR.G.S. Prabha Littis Malar (The Bioscan, 2026)
Linked zein nanoparticles (LZNPs) are considered to be the promising biopolymeric nanocarrier because of its biocompatibility, stability, and the potential of the nanocarrier to deliver drugs more efficiently. LZNPs were produced and their biological properties and molecular docking were thoroughly examined in this work. LZNPs were evaluated as cytotoxic to cancer cell lines and found to have a significant dose- dependent inhibitory effect with a better IC50 than native zein nanoparticles. The uptake by cells was confirmed to be efficient, thus their applicability in targeted delivery. Also, antioxidant and antimicrobial tests demonstrated significant biological activity, which demonstrates the multifunctional characteristics of LZNPs. Molecular docking experiments were conducted to examine the interaction of LZNP- associated bioactive compounds with the target proteins of interest in cancer progression. The docking products displayed high binding affinities and this was backed by the hydrogen bonding and the hydrophobic interaction and therefore indicated a stable ligand–protein complex formation. Altogether, this work proves that LZNPs have more favorable biological activity and favorable interactions on a molecular level and can be used as a promising option in nanomedicine in the future, especially in cancer treatment and targeted drug delivery systems.